OOS or MUD: unclear thinking is the problem - Dodwell, Peter (New Zealand medical journal, 2003)
Responding to reports about deep vein thrombosis and various environments (such as airliners), the authors discard terms such as 'economy class syndrome' and offer the witty and instructive acronym, SIT: seated immobility thromboembolism.3 Similarly constructive thinking might eliminate 'OOS' - a term with no further value. [...]the OSH/ACC guidelines already use two layers of this flawed approach to syndrome terminology.6 Unnecessary blurring of boundaries between genuine syndromes is further reason to reject the term 'OOS' from serious scientific writing, and I am pleased that vague and misleading terms of this sort were avoided in a recent paper on the subject.7 Peter Dodwell Occupational Physician Wellington References: 1. In: Kuorinka I, Forcier I. Work-related musculoskeletal disorders: a reference book for prevention.